Comparison Analysis of Sustainable Banking Performance of Sharia Bank and Conventional Bank as Members of First Movers on Sustainable Banking in Indonesia Period 2017-2020 - Dhea Rizqi Karisma; Lina Nugraha Rani (Universitas Airlangga, 2023)
ABSTRACTThis study aimed to analyze the comparison of the sustainable banking performance of Islamic banks with conventional banks as members of the first movers on sustainable banking in Indonesia for the 2017-2020 period. In this study, a quantitative approach was used using content analysis techniques and the Mann-Whitney U test. The research was conducted to determine the relationship between the dependent variable Sustainable Banking Performance (SBPF) and the independent variables consisting of SBPF Indicators (Indicators of Sustainable Banking Performance). The data used was secondary data in the form of sustainability reports and bank annual reports obtained from the bank's official website. The population in this study was the banking industry in Indonesia and the sample used was 8 member banks of First Movers on Sustainable Banking, namely Bank Muamalat, BRI Syariah, Mandiri, BRI, BNI, BCA, BJB and Bank AGI in 2017-2020. The results obtained are that 8 member banks of First Movers on Sustainable have been able to implement the practice of SBPF very well, BRI and BNI are at substantial adoption plus 5 other banks are at satisfactory adoption and AGI is at the adoption level. Furthermore, there is no significant difference from the SBPF based on Conventional Banks and Islamic Banks.Keywords: Sustainable Development, First Movers on Sustainable Banking, Sustainable banking, Sustainable Banking Performance (SBPF) ABSTRAKPenelitian ini bertujuan untuk menganalisis perba`ndingan sustainable banking performance bank syariah dengan bank konvensional sebagai angggota first movers on sustainable banking di Indonesia periode 2017-2020. Pada penelitian ini menggunakan pendekatan kuantitatif dengan teknik Content Analysis dan uji Mann-Whitney U Test. Penelitian dilakukan untuk mengetahui hubungan antara variabel dependen Sustainable Banking Performance (SBPF) dan variabel independen yang terdiri yaitu Indikator SBPF (Indicators Sustainable Banking Performance). Data yang digunakan merupakan data sekunder berupa laporan keberlanjutan dan laporan tahunan bank yang didapat dari situs web resmi bank. Populasinya adalah industri perbankan di Indonesia dan sampel yang digunakan adalah 8 bank anggota First Movers on Sustainable Banking yaitu Bank Muamalat, BRI Syariah, Mandiri, BRI, BNI, BCA, BJB dan Bank AGI pada tahun 2017-2020. Hasilnya 8 bank anggota First Movers on Sustainable sudah mampu menerapkan praktek SBPF dengan sangat baik, BRI dan BNI yang berada pada adopsi substansial ditambah 5 Bank lainya berada pada adopsi memuaskan dan AGI pada tingkat mulai mengadopsi. Selanjutnya tidak ada perbedaan yang signifikan dari SBPF berdasarkan Bank Konvensional dan Bank Syariah.Kata Kunci: Pembanguna Berkelanjutan, First Movers on Sustainable Banking, Sustainable banking, Sustainable Banking Performance(SBPF)